Effects of Irisin Compared with Exercise on Specific Metabolic and Obesity Parameters in Female Mice with Obesity - Ozgor, Bahar Yuksel; Demiral, Irem; Zeybek, Umit; Celik, Faruk; Buyru, Faruk; Yeh, John; Bastu, Ercan (MARY ANN LIEBERT, INC, 2020)
Objective: We aimed to analyze the changes in metabolic parameters after administration of irisin to obese female mice. Materials and Methods: Sixty mice aged 5-6 weeks were randomized into three groups as irisin, exercise, and control. The control and irisin group remained sedentary, whereas the exercise group started free wheel exercising 6 weeks after the start of the study. The irisin group received irisin after 20 weeks. All mice were sacrificed at the 22nd week of the study, and obesity-related metabolic parameters were analyzed. Results: There was no significant difference between the irisin and exercise groups in weight gain (P > 0.05). By contrast, weight gain in the control group was significantly higher compared with the irisin and exercise groups (P < 0.05). Serum bone morphogenetic protein (BMP), ghrelin, insulin, kisspeptin, leptin, and visfatin levels were statistically lower in the irisin and exercise groups compared with the control group, but no significance was detected between the irisin and exercise groups (P < 0.05 for all parameters). Conclusion: Similar to the effect of exercise, irisin injections resulted in the amelioration of certain obesity-related parameters such as the concentration of adipokines, BMP4, insulin, and ghrelin. Its role as a potential alternative to exercise needs to be further studied.
Keywords: irisin; obesity; adipokines; BMP4; ghrelin